¿Puede el feminismo vencer al populismo? Avances populistas de derecha y contestaciones interseccionales en las Américas - Roth, Julia (Ensayos InterAmericanos, 2020)
Recently, far-right candidates, such as Donald Trump in the USA and Jair Bolsonaro in Brazil were elected regardless of the scandals they had caused with their openly sexist and racist comments. Likewise, the electoral success of both presidents was opposed by widespread intersectional feminist protests. Thus, this essay pursues a double objective: first, to examine the logic and the role of gender for (right-wing) populism with the aim of re-evaluating the phenomenon and amplifying the theories towards more complex forms of description and analysis. Secondly, the essay outlines spaces and practices of resistance which also draw on gender politics (or make resistance against anti-sexism their point of departure). Based on the assumption that gender is not a side effect or a minor aspect of current populist rhetoric, it is argued that gender provides a fundamental and central stage for the current struggles for cultural hegemony that numerous societies currently find themselves confronted with in the light of precariousness and neoliberal crises. Thus, an intersectional approach towards gender in populism not only enriches the field of studying but may also provide an innovative parameter for a re-evaluation of the phenomenon and the theorisation of (right-wing) populism.